Evaluating Evidence of Mechanisms in Medicine : Principles and Procedures - Parkkinen, Veli-Pekka; Wallmann, Christian; Wilde, Michael; Clarke, Brendan; Illari, Phyllis; Kelly, Michael P; Norell, Charles; Russo, Federica; Shaw, Beth; Williamson, Jon (Cham Springer Nature, 2018)
Philosophy; Medicine$1 (BPhilosophy; Epistemologys
English
Keywords: Philosophy; Philosophy: epistemology & theory of knowledge; Philosophy; Medicine$1 (BPhilosophys; Epistemology